China and Brazil's infrastructure initiatives and the role of regional counterparts - María Antonia Gwynn (University of Oxford, Global Economic Governance Programme (GEG), 2017)
Emerging countries, like China or Brazil, are no different from powerful western countries in that they too use a variety of strategies to pursue their interests. To assess the utility and consequences of these strategies, I propose to focus on how these strategies will impact their less powerful regional counterparts. This is a shift away from the traditional perspective of considering powerful countries vis a vis the increasing power of emerging countries. Furthermore, by concentrating on how smaller and less powerful countries are affected by these strategies, the likelihood of success of these strategies can be predicted to some extent, as no state-strategy can be carried out without at least some support of other countries.
Keywords: 330